Can delirium tremens be seen in young patients: an assesment including - Köroğlu, Gültürk; Mırsal, Hasan; Kalyoncu, Ö. Ayhan; Beyazyürek, Mansur (Journal of Dependence, 2008)
Alcohol withdrawal delirium (Delirium Tremens) is a complication, which could be seen %5 of patients hospitalized for alcohol dependence. It is a life threating condition.. It could appear in several hours after reduction or droping of alcohol. It mostly appears in the first 2-4 days of the treatment. The clinical symtomps are confusion, increase of psychomotor activation, autonomic signs (increase of blood pressure, sweating, palpitation, ect.), hallucinations, especially persecutary delusions, tremor and seizure. Alcohol withdrawal delirium has been observed in patients with high consumption at 40-50 ages. In pscyhiatric publications, several delirium tremens cases with elderly patients can be seen, however there are fewer studies with younger patients. The aim of this study is implying the contents of delirium tremens cases in younger ages. These cases consist of 5 male patients between 2729 years old, who are inpatient between 1996-2006 on Foundation of Balikli Rum Hospital, Anatolia Clinics Alcohol Treatment Center, with alcohol dependancy and alcohol withdrawal delirium diagnosis. The files of the patients are scanned retrospectively and sociodemographical data, alcohol use habits, laboratory rates, physical diseases, psychometric tests and comorbid psychiatric disaeses are observed. As a result, after alcohol intake immediate high consumption of alcohol and depression has been observed in younger people with delirium tremens diagnosis.